Z세대 간호대학생의 내현적 자기애와 숏폼 과의존 간의 관계에서 정서조절곤란과 지연행동의 매개효과 - Park, Wanju; Park, Sangeon; Kim, Sumin; Kim, Yongbeom; Son, Bomin; Yoo, Eunjin; Lee, Somin (Journal of Korean Academy of Psychiatric & Mental Health Nursing (JKPMHN), 2026)
Purpose: This study examined the mediating effects of difficulties in emotion regulation and procrastination on the relationship between covert narcissism and short-form video overdependence among Generation Z nursing students. Methods: Participants were 173 Generation Z nursing students recruited from nursing colleges in 11 cities across South Korea. Data were collected from June 1 to July 27, 2025, using self-report questionnaires. Statistical analyses were conducted using IBM SPSS Statistics 28.0. Differences in variables were examined using t-tests and ANOVA, and mediating effects were tested using Hayes' PROCESS macro Model 4 with the bootstrapping method. Results: Covert narcissism was significantly positively correlated with short-form video overdependence (r=.69, p<.001), difficulties in emotion regulation (r=.84, p<.001), and procrastination (r=.60, p<.001). Difficulties in emotion regulation (ß=.38, p<.001) and procrastination (ß=.14, p=.045) were found to partially mediate the relationship between covert narcissism and short-form video overdependence. The final model accounted for 55.0% of the variance in short-form video overdependence (R2=.55, p<.001). Conclusion: The findings suggest that difficulties in emotion regulation and procrastination play significant mediating roles in the association between covert narcissism and short-form video overdependence. Educational interventions targeting these factors may help prevent excessive short-form video use among Generation Z nursing students.